415. A WEBCAST FOR THE EDUCATION AND INFORMATION OF PATIENTS WITH BARRETT'S ESOPHAGUS AND BARRETT'S CANCER. (24th September 2022) - Etzold, Christian; Gockel, Ines; Thieme, René
Abstract: To provide expert knowledge to patients becomes more and more important, especially during the Sars-CoV-2 pandemics, where self-helping groups could not meet and on-site information events could not take place. We discovered a need due to patients' uninformedness about diagnostic procedures, treatment options and advice for disease prevention or special nutrition and medications after the diagnosis of Barrett's esophagus and Barrett's cancer. A webpage was created, including a video streaming platform (https://webcast.barrett-initiative.de/ ). The events were performed live with the opportunity to ask questions via the chat function. Vimeo was used for the live streaming. Three to four lecturers were invited and one moderator organized the sequence of talks and questions. Additionally, the webpage is contains an encyclopedia, to explain disease related terms in a patient-orientated language. The invitation was done based on our nation-wide patient network based on genes for barrett's (g4b) study https://www.barrett-konsortium.de/ . Patients used a desktop computer (65%), mobile phones (28%), and tablets (7%) to join the video sessions. The lecture series was started with a kick-off event in September 2021 to give a bright overview about reflux, Barrett's esophagus und Barrett's cancer. Four special topic events were conducted, dealing with tumor biology, cancer prevention, diagnostics needed for the correct staging and how the diagnostic will guide the therapy by explaining the expertise review board, discussing operability and prehabilitation. The series will be continued by the endoscopic and surgical treatment options. There were 1, 100 views to the webpage. While during the kick-off 204 patients were online, approx. 71 to 171 patients saw the following events during the live sessions. Based on the questions by our patients and the continuous participation at our livestream events, we discovered an urgent need to provide a platform to patients, where they can find disease specific information in a patients-oriented language. Therefore, all lectures were deposited to a media archive where they are available to patients. We implemented our webcast project as a growing platform to cover aspects from the disease development, to diagnosis, treatment, and follow-up care.